SWITCH: A Randomised, Sequential, Open-label Study to Evaluate the Efficacy and Safety of Sorafenib-sunitinib Versus Sunitinib-sorafenib in the Treatment of Metastatic Renal Cell Cancer - Eichelberg, Christian; Vervenne, Walter L.; De Santis, Maria; Von Weikersthal, Ludwig Fischer; Goebell, Peter; Lerchenmueller, Christian; Zimmermann, Uwe; Bos, Monique M. E. M.; Freier, Werner; Schirrmacher-Memmel, Silke; Staehler, Michael; Pahernik, Sascha; et al. (European Urology, 2015)
Understanding how to sequence targeted therapies for metastatic renal cell carcinoma (mRCC) is important for maximisation of clinical benefit.To prospectively evaluate sequential use of the multikinase inhibitors sorafenib followed by sunitinib (So-Su) versus sunitinib followed by sorafenib (Su-So) in patients with mRCC.The multicentre, randomised, open-label, phase 3 SWITCH study assessed So-Su versus Su-So in patients with mRCC without prior systemic therapy, and stratified by Memorial Sloan Kettering Cancer Center risk score (favourable or intermediate).Patients were randomised to sorafenib 400mg twice daily followed, on progression or intolerable toxicity, by sunitinib 50mg once daily (4 wk on, 2 wk off) (So-Su), or vice versa (Su-So).The primary endpoint was improvement in progression-free survival (PFS) with So-Su versus Su-So, assessed from randomisation to progression or death during second-line therapy. Secondary endpoints included overall survival (OS) and safety.In total, 365 patients were randomised (So-Su, n=182; Su-So, n=183). There was no significant difference in total PFS between So-Su and Su-So (median 12.5 vs 14.9 mo; hazard ratio [HR] 1.01; 90% confidence interval [CI] 0.81-1.27; p=0.5 for superiority). OS was similar for So-Su and Su-So (median 31.5 and 30.2 mo; HR 1.00, 90% CI 0.77-1.30; p=0.5 for superiority). More So-Su patients than Su-So patients reached protocol-defined second-line therapy (57% vs 42%). Overall, adverse event rates were generally similar between the treatment arms. The most frequent any-grade treatment-emergent first-line adverse events were diarrhoea (54%) and hand-foot skin reaction (39%) for sorafenib; and diarrhoea (40%) and fatigue (40%) for sunitinib.Total PFS was not superior with So-Su versus Su-So. These results demonstrate that sorafenib followed by sunitinib and vice versa provide similar clinical benefit in mRCC.We investigated if total progression-free survival (PFS) is improved in patients with advanced/metastatic kidney cancer who are treated with sorafenib and then with sunitinib (So-Su), compared with sunitinib and then sorafenib (Su-So). We found that total PFS was not improved with So-Su compared with Su-So, but both treatment options were similarly effective in patients with advanced/metastatic kidney cancer.ClinicalTrials.gov identifier NCT00732914, www.clinicaltrials.gov.
EVALuna2:16339